Population genetic inference from genomic sequence variation - Pool, John E.; Hellmann, Ines; Jensen, Jeffrey D.; Nielsen, Rasmus (Genome Research, 2010)
Population genetics has evolved from a theory-driven field with little empirical data into a data-driven discipline in which genome-scale data sets test the limits of available models and computational analysis methods. In humans and a few model organisms, analyses of whole-genome sequence polymorphism data are currently under way. And in light of the falling costs of next-generation sequencing technologies, such studies will soon become common in many other organisms as well. Here, we assess the challenges to analyzing whole-genome sequence polymorphism data, and we discuss the potential of these data to yield new insights concerning population history and the genomic prevalence of natural selection.
10.1101/gr.079509.108